Survival Strategies of Tenant Farmers: The Interconnection Between Personal Characteristics and Environmental Factors - Yuyun Puspita Ningtyas; Anik Widiastuti; Moh Irsyad Fahmi MR (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2025)
This research examines the survival strategies of poor tenant farmers in Ngombol Village, Purworejo, Central Java, and investigates the relationship between farmers' personal characteristics and environmental factors in shaping these strategies. Using a qualitative descriptive approach, the study involved five poor tenant farmers selected through purposive sampling. Data collection was conducted through observation, semi-structured interviews, and documentation. The results show that poor tenant farmers implement three survival strategies: active strategies (increasing income sources through odd jobs or small businesses), passive strategies (utilizing harvest yields for personal consumption and reducing expenditures), and network strategies (utilizing social capital to obtain loans or assistance). The research reveals that tenant farmers with vocational high school education and skills outside the agricultural sector have better survival strategies. Their interactions with natural, economic, social, and cultural environments also play important roles in shaping survival strategies. Ownership of assets such as houses, vehicles, and livestock serve as evidence of successful implemented strategies. These findings highlight the importance of improving skills and education for poor tenant farmers to strengthen their economic resilience.